Preclinical models derived from endoscopic ultrasound-guided tissue acquisition for individualized treatment of pancreatic ductal adenocarcinoma - Tong, Ting; Zhang, Chao; Li, Jingbo; Deng, Minzi; Wang, Xiaoyan (Frontiers in Medicine, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy with poor outcomes. Although the management strategies have evolved in recent years, the PDAC 5-year survival rate remains at only 9%; it may become the second leading cause of cancer death in the USA by 2030. Only 15–20% of PDAC patients are eligible to undergo surgery; diagnostic biopsies and individualized treatment present a more significant challenge for the remaining group. Endoscopic ultrasound-guided tissue acquisition (EUS-TA) has been widely used in the diagnosis of pancreatic masses. With the advancement of this sampling technique, adequate specimens can be obtained from all patients with PDAC in both early and late clinical stages. Recent data suggest that the specimens obtained from EUS-TA might be used to establish viable preclinical models, which conserve the genetic mutation and preserve the heterogeneity of the original tumors. Additionally, any drug sensitivity evident in the EUS-TA-derived preclinical models might predict the clinical response, thus guiding the prospective therapeutic selection. As we move toward the era of precision medicine, this review provides an update on the role of EUS-TA as a method for obtaining genetic material used in preclinical models that can assess and stratify individuals according to their individual cancer biology.